Genetic variation of endangered Jankowski’s Bunting (Emberiza jankowskii): High connectivity and a moderate history of demographic decline - Huang, Long; Feng, Guochen; Li, Dan; Shang, Weiping; Zhang, Lishi; Yan, Rongfei; Jiang, Yunlei; Li, Shi (Frontiers in Ecology and Evolution, 2023)
Introduction Continued discovery of “mismatch” patterns between population size and genetic diversity, involving wild species such as insects, amphibians, birds, mammals, and others, has raised issues about how population history, especially recent dynamics under human disturbance, affects currently standing genetic variation. Previous studies have revealed high genetic diversity in endangered Jankowski’s Bunting. However, it is unclear how the demographic history and recent habitat changes shape the genetic variation of Jankowski’s Bunting. Methods To explore the formation and maintenance of high genetic diversity in endangered Jankowski’s Bunting, we used a mitochondrial control region (partial mtDNA CR) and 15 nuclear microsatellite markers to explore the recent demographic history of Jankowski’s Bunting, and we compared the historical and contemporary gene flows between populations to reveal the impact of habitat change on population connectivity. Specifically, we aimed to test the following hypotheses: (1) Jankowski’s Bunting has a large historical Ne and a moderate demographic history; and (2) recent habitat change might have no significant impact on the species’ population connectivity. Results The results suggested that large historical effective population size, as well as severe but slow population decline, may partially explain the high observable genetic diversity. Comparison of historical (over the past 4Ne generations) and contemporary (1–3 generations) gene flow indicated that the connectivity between five local populations was only marginally affected by landscape changes. Discussion Our results suggest that high population connectivity and a moderate history of demographic decline are powerful explanations for the rich genetic variation in Jankowski’s Bunting. Although there is no evidence that the genetic health of Jankowski’s Bunting is threatened, the time-lag effects on the genetic response to recent environmental changes is a reminder to be cautious about the current genetic characteristics of this species. Where possible, factors influencing genetic variation should be integrated into a systematic framework for conducting robust population health assessments. Given the small contemporary population size, inbreeding, and ecological specialization, we recommend that habitat protection be maintained to maximize the genetic diversity and population connectivity of Jankowski’s Bunting.